THE REALITY OF MAKING LIBRARY AS A LEARNING RESOURCES FOR STUDENTS IN READING ENGLISH AT SMA NEGERI 1 LAHEWA IN 2023/2024 - Gea, lisnayanti; Waruwu, Yaredi; Harefa, Trisman; Zega, Riswan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2024)
This study aimed to find out the student's views on the school library as a learning resource for reading English, the involvement of English teachers in making the school library as a learning resource for students to read English and the availability of school library collections can be used as a learning resource for students to read English. This study used a descriptive qualitative method with the research subjects being students, an English teacher, and the head of the library at SMA Negeri 1 Lahewa. Data were collected through observation, interview, and documentation techniques. Data analysis was conducted through the stages of data reduction, data display, and verification or conclusion. The results showed that students of SMA Negeri 1 Lahewa have not fully utilized the school library as an English learning resource. From the available data, only 37.83% of students have used the library as a learning resource, while the others (62.16%) have not optimally utilized the facility. The main obstacles identified were the inadequate library opening schedule and the limited collection of English books. The involvement of the English teacher in making the school library a learning resource for students in reading English at SMA Negeri 1 Lahewa has played a quiet role, providing explanations about the library, inviting students to visit the library to learn together, sharing knowledge, look for book references for assignments and inviting students to make reading book reports containing summaries of books. Then, the availability of book collections at SMA Negeri 1 Lahewa library did not provide enough for the learning needs of students in reading English. It is supported by students' statements during interviews that most of them found the difficultness to get the appropriate English books.